Formulasi Sediaan Krim dari Ekstrak Kulit Batang Menteng (Baccaurea racemosa) - Vonny Kurnia Utama; Kony Putriani; Sabrina Hayati (LPPM Universitas Abdurrab, 2024)
Stem bark of the menteng (Baccaurea racemosa) contains antioxidant phenolic and flavonoid compounds capable of stopping free radical chain reactions. This research aims to make a formula for cream preparation and to find out the antioxidant activity of cream extract from the stem bark of the menteng (Baccaurea racemosa). The study used experimental methods to make a 96% ethanol extract cream with concentrations of 0,5%, 1,5%, and 3%. The results of a semisolid shaped organoleptic test with a typical fragrance of brown, brown, and old brown brown bark extract, homogenity tests F0, F1, F2, and F3, are homogeneous. The pH tests F0 (5), F1 (4,5), F2 (4,7) and F3 (4,8). The spreadability tests F0 (6,2 cm), F1 (6,1 cm), F2 (5,9 cm) and F3 (5,6 cm). Viscosity tests F0 (887,73 cPs), F1 (748,06 cPs), F2 (839,43cPs) and F3 (817,03cPs). Testing antioxidant activity using UV-Vis spectroscopic photometers obtained a wavelength of 516,80 nm with an absorption value of 0,725 in formula 1 (extract concentration of 0,5%) obtained an IC50 value of 51,41, in formula 2 (extract concentration of 1,5%) obtained an IC50 value of 63,43, and in formula 3 (extract concentration of 3%) obtained an IC50 value of 48,91. The antioxidant content of formulas 1 and 2 has strong antioxidant activity whereas formula 3 has a significant amount of antioxidant activity.